Être tuteur en apprentissage par problèmes : quels styles d’animation ? - Christelle Lison; Denis Bédard; Josée-Anne Côté (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
As part of a professionalizing logic, several institutions have chosen to implement more learner-centered and skills-centered teaching methods, including problem-based learning. In doing so, it appears differences in tutors’ (teachers) practice. In this paper, we propose an analysis of animation styles adopted by tutors from medicine and engineering.